Ảnh hưởng của sự hỗ trợ xã hội đến căng thẳng trong công việc: Một nghiên cứu thường nhật - Ma Thế , Ngàn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Based on the Conservation of Resources Theory (Conservation of Resources Theory – COR) (Hobfoll, 1989), the current study hypothesized a direct effect of daily social support on employee stress and that daily positive emotion is a mediator of this relationship. In addition, the study also hypothesized that daily job stress is dependent on a cross-level interaction between work-home boundary management and daily social support. The hypotheses were tested using data from a diary survey with 45 respondents who participated in 10 consecutive working days. The results showed that all research hypotheses were supported by research data. Study implications and suggestions are also discussed.
Keywords: Social support; Positive emotion; Job stress; Diary study